Static vs. dynamic agglomeration economies. Spatial context and structural evolution behind urban growth. (26th October 2015) - Camagni, Roberto; Capello, Roberta; Caragliu, Andrea; Meijers, Evert; Burger, Martijn
Abstract: Critically assessing and integrating the existing literature on static agglomeration economies, this paper overcomes the agglomeration‐growth shortcut actually present in the literature by underlying the role of dynamic agglomeration economies and by empirically identifying their determinants. These latter consist in the quality of the activities hosted, the quality of production factors, the density of external linkages and co‐operation networks, and the characteristics of the overall urban system in which the city is located. These factors are expected to increase productivity and long‐term 'structural dynamics' processes of urban transformation. Theoretical expectations are validated through an econometric analysis on 136 European large urban zones.